FOXO3a acetylation regulates PINK1, mitophagy, inflammasome activation in murine palmitate‐conditioned and diabetic macrophages. Issue 3 (20th July 2021) - Gupta, Priya; Sharma, Gaurav; Lahiri, Amit; Barthwal, Manoj Kumar
Abstract: Nucleotide‐binding oligomerization domain, leucine‐rich repeat, and pyrin domain containing 3 inflammasome and mitophagy play an important role in cytokine release and diabetes progression; however, the role of saturated fatty acid that is induced under such conditions remains little explored. Therefore, the present study evaluates mechanisms regulating mitophagy and inflammasome activation in primary murine diabetic and palmitate‐conditioned wild‐type (WT) peritoneal macrophages. Peritoneal macrophage, from the diabetic mice and WT mice, challenged with LPS/ATP and palmitate/LPS/ATP, respectively, showed dysfunctional mitochondria as assessed by their membrane potential, mitochondrial reactive oxygen species (mtROS) production, and mitochondrial DNA (mtDNA) release. A defective mitophagy was observed in the diabetic and palmitate‐conditioned macrophages stimulated with LPS/ATP as assessed by translocation of PTEN‐induced kinase 1 (PINK1)/Parkin or p62 in the mitochondrial fraction. Consequently, increased apoptosis‐associated speck‐like protein containing a caspase recruitment domain (ASC) oligomerization, caspase‐1 activation, and IL1β secretion were observed in LPS/ATP stimulated diabetic and palmitate‐conditioned macrophages. LPS/ATP induced Forkhead box O3a (FOXO3a) binding to PINK1 promoter and increased PINK1 mRNA expression in WT macrophages. However, PINK1 mRNA and protein expression were significantly decreased in diabetic and palmitate‐conditioned macrophages in response to LPS/ATP. Palmitate‐induced acetyl CoA promoted FOXO3a acetylation, which prevented LPS/ATP‐induced FOXO3a binding to the PINK1 promoter. C646 (P300 inhibitor) and SRT1720 (SIRT1 activator) prevented FOXO3a acetylation and restored FOXO3a binding to the PINK1 promoter, PINK1 mRNA expression, and mitophagy in palmitate‐conditioned macrophages treated with LPS/ATP. Also, a significant decrease in the LPS/ATP‐induced mtROS production, mtDNA release, ASC oligomerization, caspase‐1 activation, and IL‐1β release was observed in the palmitate‐conditioned macrophages. Similarly, modulation of FOXO3a acetylation also prevented LPS/ATP‐induced mtDNA release and inflammasome activation in diabetic macrophages. Therefore, FOXO3a acetylation regulates PINK1‐dependent mitophagy and inflammasome activation in the palmitate‐conditioned and diabetic macrophages. Graphical Abstract: In palmitate‐conditioned wild type and diabetic mice macrophages, FOXO3a acetylation inhibits PINK1 expression and mitophagy leading to enhanced mtROS, mtDNA release, and inflammasome activation.